The delay of breast cancer diagnosis during the COVID-19 pandemic in São Paulo, Brazil - Tachibana,Bruna Mayumi Takaki (2021)
ABSTRACT Objective To evaluate the impact of COVID-19 pandemic on breast cancer diagnosis in a breast imaging center. Methods This was a retrospective cohort study that included women submitted to breast exams and procedures in a private hospital in São Paulo, SP, Brazil, as from the period of most strict social isolation measures, in 2020 (separated in first period of social isolation, March 24 to June 21, 2020, and second period, June 22 to December 31, 2020), as compared to the same period in 2019. The number of exams, cancer detection rates, pathologic findings and risk factors were analyzed. Results A total of 32,144 patients were included in the study. Breast imaging exams and procedures decreased by 78.9% in the first period, and 2.7% in the second period, in 2020. By the end of 2020, the number of breast cancer lesions detected was just six cases less than in 2019, although the number of patients submitted to mammograms was 35% lower. Conclusion There was a drop in number of breast exams and cancer diagnoses in the first 90 days of the pandemic. The decrease in diagnosis of cancer was partially compensated in the second period, but the number of patients submitted to mammograms by the end of 2020 was lower, still considering a large number of patients with delayed exams.